Economic Empowerment Strategy in Defense Entrepreneurship to Support the Universal People's Defense and Security System - Mahroza, Jonni; Prakoso, Lukman Yudho; Yulivan, Ivan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The limitation of Defense budget creates its own problems in facing factual and potential threats. The purpose of writing this article is to analyze the Impact of Economic Empowerment Strategy in Defense Entrepreneurship to Support the Total People's Defense and Security System. And Formulation of Economic Empowerment Strategy in Defense Entrepreneurship to Support the Total People's Defense and Security System. The results of the study are that the implementation of economic empowerment strategy requires planned steps, including strategic planning, infrastructure development, strong partnerships, and periodic monitoring and evaluation. Investment in production capacity and technology, as well as support for education and training programs, are key steps to achieving defense goals.